Macrophage-derived chemokines in T cell regulation: implications for cancer immunotherapy - Zhang, Kunpeng; Liu, Jingjing; Liu, Qi; Zhu, Ningning; Ye, Baodong (Frontiers in Immunology, 2026)
Macrophages are pivotal regulators of immunity, with intercellular communication being a central mechanism of their function. Among these communications, chemokines act as critical messengers in macrophage-T cell crosstalk. This review systematically elucidates the notable roles of macrophage-derived chemokines in modulating T cell homeostasis, particularly concentrating on their influence on both CD4+ and CD8+ T cell differentiation, proliferation, exhaustion, secretory activity, metabolic reprogramming (involving glycolysis and OXPHOS), chemotaxis, and memory formation. In the tumor microenvironment (TME), the dualistic nature of chemokines was highlighted: tumor-associated macrophages (TAMs) could secrete immunosuppressive factors, such as CCL22 and CCL5, recruiting inhibitory cells and inducing CD8+ T cell exhaustion. In contrast, M1-like macrophages could produce CXCL9 and CXCL10, activating effector CD8+ T cells, thereby enhancing anti-tumor immunity. Finally, the promising therapeutic potential of targeting specific chemokine signaling axes, such as CCL2/CCR2 and CXCL10/CXCR3, was discussed as a strategy to improve the efficacy of cancer immunotherapy.